Tobacco use and second-hand smoke exposure in young adolescents aged 12-15 years: data from 68 low-income and middle-income countries - Prof. Bo Xi, PhD; Yajun Liang, PhD; Prof. Yunxia Liu, PhD; Yinkun Yan, PhD; Min Zhao, PhD; Chuanwei Ma, MS; Prof. Pascal Bovet, MD (Elsevier, 2016)
Background: Tobacco use is an important risk factor for non-communicable diseases worldwide. However, the global extent and prevalence of tobacco use in adolescents is poorly described. Using previously collected survey data, we aimed to assess tobacco use and second-hand smoke exposure in young adolescents aged 12-15 years in 68 low-income and middle-income countries. Methods: We used data from the Global School-based Student Health Survey (2006-13) and the China Global Tobacco Youth Survey (2013), which are school-based surveys of young adolescents aged 12-15 years that assess health behaviours using a standardised, anonymous, self-reported questionnaire. We calculated the prevalence of current tobacco use and exposure to second-hand smoke in young adolescents from 68 low-income and middle-income countries that collected these data in the surveys. We used a multilevel model to estimate the association between parental tobacco use, second-hand smoke, and adolescent tobacco use, adjusting for sex, age, school, school class, country's purchasing power parity, smoking initiation age, national prevalence of tobacco use among adults, year the WHO FCTC was ratified for each country, proxy of socioeconomic status, and survey year. Findings: The mean prevalence of current tobacco use was 13·6%, ranging from 2·8% in Tajikistan to 44·7% in Samoa. In most countries, the prevalence of tobacco use was higher for boys than girls, and higher for adolescents aged 14-15 years than for those aged 12-13 years. The overall prevalence of second-hand smoke exposure was 55·9%, ranging from 16·4% in Tajikistan to 85·4% in Indonesia. Parental tobacco use (as reported by the young adolescents), especially maternal use, was associated with tobacco use in young adolescents (odds ratio 2·06, 95% CI 1·93-2·19, for maternal and 1·29, 1·23-1·35 for paternal use). Second-hand smoke exposure was also a risk factor for young adolescents' tobacco use (2·56, 2·43-2·69). However, the prevalence of tobacco use was not associated with a country's purchasing power parity. Interpretation: Tobacco use and second-hand smoke exposure were frequent among young adolescents aged 12-15 years in low-income and middle-income countries. Parental tobacco use and second-hand smoke exposure were strongly associated with young adolescents' tobacco use. The data emphasise the need to strengthen tobacco control interventions and programmes in young adolescents from low-income and middle-income countries. Funding: This work was partly supported by the Young Scholars Program of Shandong University (2015WLJH51), the Shandong Provincial Natural Science Foundation (ZR2012HQ033), and the National Natural Science Foundation (81302496).